SFB flagellin mediates cell adhesion, endocytosis and immune regulation in germ-free mice - Chen, Huahai; Wu, Liu; Cao, Xiongyu; Li, Zongyan; Zhu, Renjun; Wang, Xiaojing; Li, Jun; Wei, Zuzhang; Yang, Dengfeng; Yin, Yeshi (Frontiers in Immunology, 2025)
IntroductionSegmented filamentous bacteria (SFB) colonization dynamics are crucial for host immune regulation. Given this, the present study specifically examined the functions of SFB flagellin in bacterial adhesion, cellular internalization, and immune modulation.MethodsLactococcus lactis and Escherichia coli were engineered to express murine and rat SFB flagellin genes. Subsequent in vitro co-culture experiments with intestinal epithelial cell lines (MODE-K and IEC-18) and germ-free mouse colonization assays were conducted. Bacterial counts, immunohistochemical analysis, the AAM-ISO-G1 and QAM-TH17–1 microarray systems, RNA sequencing and molecular docking were employed to assess the outcomes in this study.Results and discussionThe results of in vitro co-culture experiments demonstrated significantly improved bacterial adhesion capabilities mediated by SFB flagellin. Germ-free mouse colonization assays revealed prolonged fecal persistence of flagellin-expressing strains. Immunohistochemical analysis of ileal tissues showed co-localization of recombinant bacteria with the lysosomal-associated membrane protein 2 (Lamp2), confirming cellular internalization. Furthermore, mfliC3-expressing Escherichia coli exhibited active invasion into MODE-K cells. RNA sequencing analysis identified significant enrichment of Th17 cell differentiation pathways in both ileum and hepatic tissues from Lac-rfliC3-colonized mice. Correspondingly, the Lac-mfliC3 group showed elevated serum levels of Th17-associated cytokines including IFN-γ, IL-23p19, IL-17A, IL-5, and IL-6 compared to controls. Molecular docking simulations revealed high-affinity interactions between SFB flagellins and endocytic regulators endophilin A2 and αM integrin. These results demonstrate that SFB flagellin mediates bacterial-epithelial interactions through dual mechanisms of adhesion potentiation and active internalization, ultimately driving Th17-mediated immune responses.